Comparative study of Al2O3-YAG:Ce composite ceramic and single crystal YAG:Ce phosphors for high-power laser lighting. Issue 11 (1st August 2020) - Xu, Jian; Yang, Yang; Guo, Ziquan; Corell, Dennis Dan; Du, Baoli; Liu, Bingguo; Ji, Haipeng; Dam-Hansen, Carsten; Jensen, Ole B.
Abstract: Recent studies revealed that both the Al2 O3 –Y3 Al5 O12 :Ce (YAG:Ce) composite ceramic (YAG-CC) and single crystalline YAG:Ce (YAG-SC) possess very high luminescence-saturation thresholds (LSTs), which makes them promising for laser lighting applications. The present study is aimed to conduct a comparative investigation between YAG-CC and YAG-SC on aspects of the laser-pumped luminescence and the associated thermal behavior. The colorimetric and photometric properties (e.g. luminous flux/efficacy, correlated color temperature, and color rendering index) were investigated systematically, by conducting the measurements using a custom-built sphere-spectroradiometer system in the transmission mode. It was found that YAG-SC has a superior LST and it could maintain a high luminous efficacy (106 lm/W) under the irradiation of a 15.33 W blue laser, while the YAG-CC saturated at around 7.76 W. Moreover, by combining the thermal imaging data with the spectral variation of the YAG-CC, novel experimental insights into the origin of luminescence saturation were revealed and proposed as the "thermally-induced absorption saturation".